2003
DOI: 10.1074/jbc.m211339200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of a Hyperthermophilic α-Amylase with a Novel (Ca,Zn) Two-metal Center by Zinc

Abstract: The crystal structure of the ␣-amylase from the hyperthermophilic archaeon Pyrococcus woesei was solved in the presence of three inhibitors: acarbose, Tris, and zinc. In the absence of exogenous metals, this ␣-amylase bound 1 and 4 molar eq of zinc and calcium, respectively. The structure reveals a novel, activating, twometal (Ca,Zn)-binding site and a second inhibitory zincbinding site that is found in the ؊1 sugar-binding pocket within the active site. The data resolve the apparent paradox between the zinc r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 51 publications
2
88
0
1
Order By: Relevance
“…Structural studies of ␣-amylases in complex with substrate analogues have received much attention in the past decade (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The pseudotetrasaccharide inhibitor acarbose was used for the vast majority of these studies.…”
mentioning
confidence: 99%
“…Structural studies of ␣-amylases in complex with substrate analogues have received much attention in the past decade (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The pseudotetrasaccharide inhibitor acarbose was used for the vast majority of these studies.…”
mentioning
confidence: 99%
“…Stability of α-amylase activity by Ca 2+ ions at high temperatures has been reported [41]. Enhancement of amylase activity by metallic ions might be due to their ability interact with negatively charged amino acid residues such as aspartic and glutamic acid [42], thereby stabilizing and maintaining the enzyme conformation. Researchers have reported inhibition of amylase activity by Ag + , Hg 2+ , Cd 2+ , Cu 2+ , Pb 2+ , Fe 2+ , Ni 2+ , Mn 2+ and Zn 2+ ions [10,37,43].…”
Section: Characterization Of α-Amylasementioning
confidence: 99%
“…All known -amylases, with a few exceptions, contain a conserved Ca 2+ binding site which is located at the interface between domains A and B (Linden et al, 2003;Prakash & Jaiswal, 2010). In addition, -amylase produced by Bacillus thermooleovorans was found to contain a chloride ion binding site in their active site (Malhotra et al, 2000), which has been shown to enhance the catalytic efficiency of the enzyme, presumably by elevating the pKa of the hydrogen-donating residue in the active site (Prakash & Jaiswal, 2010).…”
Section: Modular Structurementioning
confidence: 99%
“…Most known -amylases, with a few exceptions, contain a conserved Ca 2+ binding site (Linden et al, 2003;Prakash & Jaiswal, 2010) which make calcium be important to the enzyme activity. In manufacture of fructose syrup, the Ca 2+ ions inhibit the glucose isomerase enzyme used in the final step of the process (Tonkova, 2006) and may lead to the formation of inorganic precipitates which have deleterious effects on fermentation and downstream processing (Kelly et al, 2009).…”
Section: Industrial Desirable Aspectsmentioning
confidence: 99%